Teori Dramaturgi Dalam Komunikasi Guru Di Yayasan Penitipan Anak Berkebutuhan Khusus - Nugroho, Latif Setyo (Jurnal Dinamika Sosial Budaya, 2023)
This study aims to determine teacher communication at the day care foundation that occurs both in the front and back areas which is then analyzed using Erning Goffman’s Dramaturgy Theory. This study uses a qualitative method. Data collection techniques were carried out by interview and observation. Data analysis is done by classifying, creating categories and describing categories or themes from the findings. As we know, Children with Special Needs (ABK) are included in 15 groups of children who are vulnerable to violence. The forms of violence experienced are also very diverse, ranging from physical, psychological violence to social barriers such as negative labeling and discrimination